Diagnosing and Managing Ischemic Stroke in Children in Limited Resources Facilities: A Case Report - Made Suadnyani Pasek; Ni Nyoman Mestri Agustini; Made Dinda Pratiwi (Ganesha Medicina, 2026)
Stroke is a significant cause of death and disability in children. Stroke is among the 10 leading causes of death in children aged 5 to 25 years. ischemic stroke is defined when a focal neurological deficit occurs that lasts more than 24 hour, with neuroimaging evidence of cerebral infarction. We report a 9-year-old boy presented to the emergency room complaining of weakness in the right half of his body. this complaint was sudden, improved for several hours, and then persisted. The patient also complained of slurred speech and a headache prior admission. Laboratory test revealed, head CT scan showed an acute cerebral infarction of the lentiform nucleus and left temporal bone. Treatment consisted of aspirin 3.5 mg/kg/day for its antiplatelet effects and intravenous citicoline 10 mg/kg every 12 hours, a neuroprotective agent that supports recovery following neurological conditions such as stroke or brain injury. The patient showed improvement on the third day of treatment, with improvement in right hemiparesis and slurred speech. Early recognition of stroke in children is crucial, along with the implementation of targeted and neuroprotective therapies.